Genetic encoding and expression of RNA origami cytoskeletons in synthetic cells - Tran, Mai P.; Chakraborty, Taniya; Poppleton, Erik; Monari, Luca; Illig, Maja; Gießler, Franziska; Göpfrich, Kerstin (Nature nanotechnology, 2025)
Bottom-up synthetic biology seeks to engineer a cell from molecular building blocks. Using DNA nanotechnology, building blocks, such as cytoskeletons, have been reverse-engineered. However, DNA nanostructures rely on chemical synthesis and thermal annealing, and therefore synthetic cells cannot produce them from their constituents such as nucleotides. Here we introduce RNA origami cytoskeleton mimics as alternative nucleic acid-based molecular hardware for synthetic cells, which we express directly inside giant unilamellar lipid vesicles (GUVs) containing a DNA template and a polymerase, chemically fuelled by feeding nucleotides from the outside. We designed RNA origami tiles that fold upon transcription and self-assemble into micrometre-long, three-dimensional RNA origami nanotubes under isothermal conditions. We observe that sequence mutations on the DNA template lead to RNA origami nanotubes and closed-ring phenotypes. Molecular dynamics simulations show that these phenotypic transitions are governed by alterations in the stability of RNA secondary structures. In addition, we achieve cortex formation with aptamer-functionalized RNA nanotubes and show that nanotube polymerization leads to membrane deformation. Altogether, our data suggest that the expression of RNA origami-based hardware will help to explore active, evolvable and RNA-based synthetic cells.